Pengaruh Kepuasan Mahasiswa terhadap Persepsi Kualitas Sistem E-Learning dengan Metode EUCS (End User Computing Satisfaction) - Achmad Fais Ghozali; Hendi Kurniyawan (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
The development of information technology has driven higher education institutions, including Islamic universities, to adopt E-Learning systems as a means to support the learning process. However, the effectiveness of these systems is largely determined by user satisfaction and their perception of system quality. This study aims to analyze the influence of student satisfaction on their perception of E-Learning system quality by employing a quantitative approach using a simple linear regression method. The population of the study consists of students from Nurul Jadid University, selected through purposive sampling, with a total of 42 respondents. The research instrument was developed based on the five dimensions of the End User Computing Satisfaction (EUCS) model. Data were collected using a Likert-scale questionnaire. The results of the analysis show that student satisfaction has a positive and significant effect on the perceived quality of the E-Learning system, with an R Square value of 0.481 and a significance level (p) < 0.001. This indicates that 48.1% of the variation in perceived system quality can be explained by user satisfaction. These findings suggest that the higher the students' satisfaction with the content, accuracy, format, ease of use, and timeliness of the system, the higher their perception of the overall quality of the E-Learning system. The study recommends further development of E-Learning systems with a stronger focus on enhancing user experience and comfort.